2021
DOI: 10.1007/s12185-021-03112-y
|View full text |Cite
|
Sign up to set email alerts
|

New routes to eradicating chronic myelogenous leukemia stem cells by targeting metabolism

Abstract: Chronic myelogenous leukemia (CML) stem cells are the cellular source of the vast majority of mature CML cells and responsible for relapse of CML disease post-tyrosine kinase inhibitor (TKI) therapy. Although mature CML cells, whose active division is driven by BCR-ABL1 oncogene-dependent signaling, are reduced by TKI therapy, CML stem cells are resistant because they become quiescent via a heretofore elusive mechanism that is independent of oncogene signaling. Recent advances in highly sensitive metabolomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…In our CML cohort, a high FAMscore also reflected enhanced fatty acid metabolism and the rapid proliferation of malignant phenotypes of CML cells. This is because CML cells require a lot of energy and promote the fluidity of cell membranes by increasing the content of unsaturated fatty acids [ 43 ]. All these indicate that the FAMscore has certain accuracy in predicting the fatty acid metabolism activity of leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our CML cohort, a high FAMscore also reflected enhanced fatty acid metabolism and the rapid proliferation of malignant phenotypes of CML cells. This is because CML cells require a lot of energy and promote the fluidity of cell membranes by increasing the content of unsaturated fatty acids [ 43 ]. All these indicate that the FAMscore has certain accuracy in predicting the fatty acid metabolism activity of leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonate lipoxygenase (ALOX5)-5 and ALOX15 are also involved in LSC self-renewal and fatty acid metabolism by changing arachidonic acid to leukotrienes such as leukotriene B4 (LTB4), which increases the expression of the leukotriene B4 receptor 2 (BLT2) in CML stem cells [ 104 , 105 ]. Moreover, lysophospholipid metabolism plays a part in the maintenance of CML stem cells and TKI resistance by regulation of lysophospholipase D activity of GDPD3 in the BCR-ABL1-independent manner signaling pathway, and FOXO3A/β-catenin interaction [ 106 ].…”
Section: Survival and Functional Resistance Of CML Lscs To Therapiesmentioning
confidence: 99%
“…The inhibition of mitochondrial function has antileukemia effects along with TKIs [ 90 ]. The important findings suggest that SIRT1 and/or elements downstream in the OXPHOS pathway may be potential therapeutic targets, for instance, inhibiting PPARγ coactivator-1α (PGC-1α) by SR-18292 in combination with TKIs could avoid CML relapse by the increase in on PGC-1 acetylation levels affected of SIRT1 [ 106 ].…”
Section: Therapeutic Implications Of CML Lscsmentioning
confidence: 99%
“…To our surprise, enforced treatment in vitro with PGE2 restored this interaction within the nuclei of Lgr4/Gpr48 -hypomorphic mutant LT-CML stem cells, but not in Gdpd3 -deficient LT-CML stem cells (where Foxo3a was inactivated in the cytoplasm). These results suggest that Gdpd3-mediated lysophospholipid metabolism may maintain the self-renewal capacity of CML stem cells by activating the stemness factors Foxo3a and β-catenin [ 14 , 15 ].…”
Section: Biological Significance Of Gdpd3 In CML Stem Cellsmentioning
confidence: 99%
“…The question then arises: What is the factor that overcomes BCR–ABL1 and suppresses Akt activation in CML stem cells such that Foxo3a is allowed to function? Our investigation revealed that lysophospholipid metabolism inhibits Akt, and that it is the lysophospholipase D enzyme Glycerophosphodiester Phosphodiesterase Domain Containing 3 (Gdpd3) that plays an essential role in maintaining stem cell quiescence and TKI resistance in CML stem cells [ 14 , 15 ]. This involvement of lysophospholipid metabolism in CML stemness opens up a new field of investigation in the realm of novel CML treatments.…”
Section: Introductionmentioning
confidence: 99%